A new species of Lasianobia Hampson, 1905 (Lepidoptera, Noctuinae) from China - Saldaitis, Aidas; Floriani, Alessandro; Ivinskis, Povilas; Babics, János (Zootaxa, 2013)
A new species, Lasianobia pensottii, from southwest China is described. The new species clearly differs in appearance and genitalia from its closest known relative L. fickleri Gyulai, Ronkay & Saldaitis, 2011 and from the sympatric L. superba (Alphéraky, 1892).